Participation in victim-offender mediation predicts less reoffending: a propensity score matched case-control study - Dijk, Jiska Jonas-van (Crime & delinquency, 2025)
Previous research on victim-offender mediation (VOM) and reoffending rates often lack valid control groups and might suffer from a self-selection bias. Moreover, VOM’s role in the criminal justice system, particularly the effect on sanctioning, has not been considered in explaining the lower reoffending rates. This research addressed these gaps, by comparing four offender groups and using propensity score matching (N = 2,907): those who participated in VOM, those unwilling, those unable due to victim refusal, and those not referred. Results replicated that VOM participation predicts lower reoffending rates, primarily due to the mediation process itself rather than self-selection. While VOM reduced the likelihood of sanctions, this did not explain the observed decrease in reoffending rates.